Stem cell-derived motor neurons from spinal and bulbar muscular atrophy patients - Christopher Grunseich; Kristen Zukosky; Ilona R. Kats; Laboni Ghosh; George G. Harmison; Laura C. Bott; Carlo Rinaldi; Ke-lian Chen; Guibin Chen; Manfred Boehm; Kenneth H. Fischbeck (Neurobiology of Disease, 2014)
Spinal and bulbar muscular atrophy (SBMA, Kennedy's disease) is a motor neuron disease caused by polyglutamine repeat expansion in the androgen receptor. Although degeneration occurs in the spinal cord and muscle, the exact mechanism is not clear. Induced pluripotent stem cells from spinal and bulbar muscular atrophy patients provide a useful model for understanding the disease mechanism and designing effective therapy. Stem cells were generated from six patients and compared to control lines from three healthy individuals. Motor neurons from four patients were differentiated from stem cells and characterized to understand disease-relevant phenotypes. Stem cells created from patient fibroblasts express less androgen receptor than control cells, but show androgen-dependent stabilization and nuclear translocation. The expanded repeat in several stem cell clones was unstable, with either expansion or contraction. Patient stem cell clones produced a similar number of motor neurons compared to controls, with or without androgen treatment. The stem cell-derived motor neurons had immunoreactivity for HB9, Isl1, ChAT, and SMI-32, and those with the largest repeat expansions were found to have increased acetylated α-tubulin and reduced HDAC6. Reduced HDAC6 was also found in motor neuron cultures from two other patients with shorter repeats. Evaluation of stably transfected mouse cells and SBMA spinal cord showed similar changes in acetylated α-tubulin and HDAC6. Perinuclear lysosomal enrichment, an HDAC6 dependent process, was disrupted in motor neurons from two patients with the longest repeats. SBMA stem cells present new insights into the disease, and the observations of reduced androgen receptor levels, repeat instability, and reduced HDAC6 provide avenues for further investigation of the disease mechanism and development of effective therapy.